Protein corona mitigates the cytotoxicity of graphene oxide by reducing its physical interaction with cell membrane. Issue 37 (28th August 2015) - Duan, Guangxin; Kang, Seung-gu; Tian, Xin; Garate, Jose Antonio; Zhao, Lin; Ge, Cuicui; Zhou, Ruhong
Abstract : While bare graphene oxide can cause serious damages on cell membranes eliciting cell death, the protein corona by serum protein dramatically enhanced cell viability, as providing an important insight for de novo design of nanomedicine. Abstract : Many recent studies have shown that the way nanoparticles interact with cells and biological molecules can vary greatly in the serum-containing or serum-free culture medium. However, the underlying molecular mechanisms of how the so-called "protein corona" formed in serum medium affects nanoparticles' biological responses are still largely unresolved. Thus, it is critical to understand how absorbed proteins on the surfaces of nanoparticles alter their biological effects. In this work, we have demonstrated with both experimental and theoretical approaches that protein BSA coating can mitigate the cytotoxicity of graphene oxide (GO) by reducing its cell membrane penetration. Our cell viability and cellular uptake experiments showed that protein corona decreased cellular uptake of GO, thus significantly mitigating the potential cytotoxicity of GO. The electron microscopy images also confirmed that protein corona reduced the cellular morphological damage by limiting GO penetration into the cell membrane. Further molecular dynamics (MD) simulations validated the experimental results and revealed that the adsorbed BSA in effect weakened the interaction between the phospholipids and graphene surface due to a reduction of the available surface area plus an unfavorable steric effect, thus significantly reducing the graphene penetration and lipid bilayer damaging. These findings provide new insights into the underlying molecular mechanism of this important graphene protein corona interaction with cell membranes, and should have implications in future development of graphene-based biomedical applications.